2014
DOI: 10.1093/eurpub/cku076
|View full text |Cite
|
Sign up to set email alerts
|

The alcohol industry, charities and policy influence in the UK

Abstract: Background: Charities exist to pursue a public benefit, whereas corporations serve the interests of their shareholders. The alcohol industry uses corporate social responsibility activities to further its interests in influencing alcohol policy. Many charities also seek to influence alcohol and other policy. The aim of this study was to explore relationships between the alcohol industry and charities in the UK and whether these relationships may be used as a method of influencing alcohol policy. Methods: The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…This obviously places researchers in perilous ethical positions, not just in relation to industry, but also (and perhaps most significantly) with respect to their colleagues in the alcohol control movement. Amid this, there is a growing body of qualitative work about the actions of industry including their funding links with charities (Lyness & McCambridge, 2014), their influence on the policy process , industry perspectives on alcohol as a problem (Baggott, 2006) and more nuanced readings that challenge the characterisation of 'Big Booze' as a monolithic . These are important contributions to the development of a science of corporate behaviour and ones that highlight the need to research in ways that tread more lightly than the stance adopted by the more adversarial alcohol control advocates.…”
Section: Moving From Adversarialism To Methodological Innovationmentioning
confidence: 99%
“…This obviously places researchers in perilous ethical positions, not just in relation to industry, but also (and perhaps most significantly) with respect to their colleagues in the alcohol control movement. Amid this, there is a growing body of qualitative work about the actions of industry including their funding links with charities (Lyness & McCambridge, 2014), their influence on the policy process , industry perspectives on alcohol as a problem (Baggott, 2006) and more nuanced readings that challenge the characterisation of 'Big Booze' as a monolithic . These are important contributions to the development of a science of corporate behaviour and ones that highlight the need to research in ways that tread more lightly than the stance adopted by the more adversarial alcohol control advocates.…”
Section: Moving From Adversarialism To Methodological Innovationmentioning
confidence: 99%
“…A charity which has previously received alcohol funding, Addaction [17], is also situated in the Proponents coalition, although more peripherally. Alcohol Concern, Alcohol Focus Scotland, are positioned centrally in the Proponents coalition with no ties to organizations in the Opponents Coalition.…”
Section: Think-tanks and Charity Organizationsmentioning
confidence: 99%
“…Previous research on alcohol policy in general, and MUP in particular, has also highlighted the importance of the alcohol industry as key influencers [16][17][18][19]. More indirect influence by industry through organizations such as think-tanks [18] and charities [17], as well as through alliances with consumer/civil society groups and engagement in social responsibility activities [19], has also been noted. More indirect influence by industry through organizations such as think-tanks [18] and charities [17], as well as through alliances with consumer/civil society groups and engagement in social responsibility activities [19], has also been noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They must emulate those who asked why 76% of third class passengers on the Titanic perished but only 39% of those in first class, 14 those who showed that inequality is "killing people on a grand scale," 15 and those who measured then exposed the human cost of austerity. 16 They must also make visible the often hidden corporate determinants of health, such as the tactics used by tobacco, 17 food, 18 and alcohol 19 industries in subverting healthy public policies.…”
mentioning
confidence: 99%